Serum Lactate Dehydrogenase Levels Reflect the Lung Injury Extension in COVID‐19 Patients at Hospital Admission - Maria Sofia Bertilacchi; Giulia Vannucci; Rebecca Piccarducci; Lorenzo Germelli; Chiara Giacomelli; Chiara Romei; Brian Bartholmai; Greta Barbieri; Claudia Martini; Michela Baccini (Immunity, Inflammation and Disease)
ABSTRACT Background Several hematological and biochemical parameters have been related to the COVID‐19 infection severity and outcomes. However, less is known about clinical indicators reflecting lung involvement of COVID‐19 patients at hospital admission. Computed tomography (CT) represents an established imaging tool for the detection of lung injury, and the quantitative analysis software CALIPER has been used to assess lung involvement in COVID‐19 patients. Herein, the relationship between the lung involvement expressed by CALIPER interstitial lung disease (ILD) percentage and a set of blood parameters related to tissue oxygenation and damage in COVID‐19 patients at hospital admission was evaluated. Methods We performed a retrospective and a prospective study involving 321 and 75, respectively, COVID‐19‐positive patients recruited from Pisa University Hospital. The association between CALIPER ILD percentages and selected blood parameters was investigated by a regression tree approach, after multiple imputations of the dataset missing values. Results High serum lactate dehydrogenase (LDH) values appeared to be predictive of high CALIPER ILD percentages at hospital admission in both retrospective and prospective datasets, even if the predictive performance of the algorithm was not optimal. Conclusions LDH levels could be evaluated as a tool for early identification of COVID‐19 patients at risk of extensive lung injury, as well as in fast screening procedures before hospitalization.